1998
DOI: 10.1099/00222615-47-7-569
|View full text |Cite
|
Sign up to set email alerts
|

Two different types of humoral immune response to Actinobacillus actinomycetemcomitans in high-responder periodontitis patients

Abstract: Actinobacillus actinomycetemcomitans is considered to be an aetiological agent in various forms of periodontitis, with serotype b-specific carbohydrate being the immunodominant antigen of A. actinomycetemcomitans Y4 in high-responder patients. Lipopolysaccharide (LPS) of the organism may also be an important antigen. The purpose of the present study was to clarify the importance of LPS as an antigen of A. actinomycetemcomitans. Twenty patients who had high antibody titres to strain Y4 were selected, and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Whether the discrepancy between their and our results was caused by differences in the study populations, simultaneous or sequential infections with strains of several A. actinomycetemcomitans serotypes could not be concluded from the results shown in those studies. Furthermore, Nakashima et al (18) found two types of high-responding patients: the first group had high IgG antibodies only against A. actinomycetemcomitans serotype b, while the other group had high IgG antibodies against strains representing serotypes a, b, and c. Their study showed that the antibodies in the first group were mainly against serotype b-specific carbohydrate, while the antibodies of the other group were mainly reactive with lipopolysaccharides of all serotypes. Although these results are slightly different from ours, they also support the variation in serum IgG levels against different strains within individuals and emphasize the importance of using a sufficient variety of strains as antigens in ELISA in order to ensure the detection of seropositive individuals.…”
Section: Vol 40 2002 Autologous Versus Reference Strains As Antigenmentioning
confidence: 99%
“…Whether the discrepancy between their and our results was caused by differences in the study populations, simultaneous or sequential infections with strains of several A. actinomycetemcomitans serotypes could not be concluded from the results shown in those studies. Furthermore, Nakashima et al (18) found two types of high-responding patients: the first group had high IgG antibodies only against A. actinomycetemcomitans serotype b, while the other group had high IgG antibodies against strains representing serotypes a, b, and c. Their study showed that the antibodies in the first group were mainly against serotype b-specific carbohydrate, while the antibodies of the other group were mainly reactive with lipopolysaccharides of all serotypes. Although these results are slightly different from ours, they also support the variation in serum IgG levels against different strains within individuals and emphasize the importance of using a sufficient variety of strains as antigens in ELISA in order to ensure the detection of seropositive individuals.…”
Section: Vol 40 2002 Autologous Versus Reference Strains As Antigenmentioning
confidence: 99%
“…The serotype-specific antigen of A. actinomycetemcomitans is the immunodominant antigen of this species (Califano et al, 1989;Sims et al, 1991;Nakashima et al, 1998). Thus, not expressing S-PA may provide the strain protection from antibody-based host responses, which could confer a competitive advantage over strains expressing this antigen.…”
Section: Discussionmentioning
confidence: 99%
“…A. actinomycetemcomitans Y4 was grown in Todd-Hewitt broth supplemented with 1% (w/v) yeast extract at 37³C in an atmosphere of 5% CO P . LPS was extracted from whole cells of A. actinomycetemcomitans by the method of Westphal et al [11], and further puri¢ed by gel ¢ltration chromatography as described previously [12]. The material from A. actinomycetemcomitans Y4 is designated Y4 LPS.…”
Section: Cell and Bacterial Strainmentioning
confidence: 99%